2022
DOI: 10.1073/pnas.2208886119
|View full text |Cite
|
Sign up to set email alerts
|

Mono-(2-ethyl-5-hydroxyhexyl) phthalate promotes uterine leiomyoma cell survival through tryptophan-kynurenine-AHR pathway activation

Abstract: Uterine leiomyoma is the most common tumor in women and causes severe morbidity in 15 to 30% of reproductive-age women. Epidemiological studies consistently indicate a correlation between leiomyoma development and exposure to endocrine-disrupting chemical phthalates, especially di-(2-ethylhexyl) phthalate (DEHP); however, the underlying mechanisms are unknown. Here, among the most commonly encountered phthalate metabolites, we found the strongest association between the urine levels of mono(2-ethyl-5-hydroxyhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 82 publications
(101 reference statements)
0
7
0
Order By: Relevance
“…Prior studies found Black individuals to have higher levels of phthalates compared with White individuals, possibly secondary to differences in use pattern of personal care products . Phthalates may potentiate fibroid growth by delaying apoptosis and promoting leiomyoma cell survival . Higher urinary levels of paraben, an estrogenic preservative, were also observed in Black individuals .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Prior studies found Black individuals to have higher levels of phthalates compared with White individuals, possibly secondary to differences in use pattern of personal care products . Phthalates may potentiate fibroid growth by delaying apoptosis and promoting leiomyoma cell survival . Higher urinary levels of paraben, an estrogenic preservative, were also observed in Black individuals .…”
Section: Discussionmentioning
confidence: 94%
“… 37 , 38 Phthalates may potentiate fibroid growth by delaying apoptosis and promoting leiomyoma cell survival. 39 Higher urinary levels of paraben, an estrogenic preservative, were also observed in Black individuals. 40 Limited data also show higher EDC levels in Chinese American female individuals.…”
Section: Discussionmentioning
confidence: 98%
“…Clinical studies have suggested that MEHHP and MECPP exposure was associated with prostate cancer [ 28 ], thyroid cancer [ 31 ], breast cancer [ 40 ] and urothelial cancer [ 53 ]. In addition, MEHHP was reported to promote the survival of leiomyoma cells by increasing cellular tryptophan uptake, kynurenine production, and activating the aryl hydrocarbon receptor pathway [ 54 ]. All of the above evidence indicated that MEHHP, MECPP and DBP are closely correlated with the development of cancer, which are consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments using human uterine leiomyoma cells demonstrated that DEHP exposure enhanced cell viability, promoted anti-apoptotic protein expression, and induced the expression of HIF-1α and COX-2 ( 32 ). Other epidemiological and in vitro studies have shown that the major DEHP metabolite, mono (2-ethyl-5-hydroxyhexyl) phthalate (MEHHP), enhances the survival of leiomyoma cells through activation of the tryptophan-kynurenine-AHR pathway ( 33 ). Additionally, analysis of the TREE cohort data revealed positive associations between certain PAE exposures and the risks of UFs and endometriosis, which may be mediated by oxidatively generated DNA damage ( 34 ).…”
Section: Introductionmentioning
confidence: 99%